1980
DOI: 10.1139/v80-017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion and methyl group rotation barriers from 13C nmr relaxation times. Norbornane and adamantane derivatives in solution

Abstract: H E L M U~ BEIERBECK. ROBERTMARTINO. and JOHN K . SAUNDERS. Can. J. Chem. 58, 102 (1980). The carbon-I3 relaxation time data for several norbornane and adamantane derivatives are presented. It is shown that the most probable principal axis of the rotational diffusion tensor is an axis which contains the centre of mass of the molecule and the heterosubstituent. The infl~lence of the C-C-H bond angle on the calculation of methyl group rotation barriers from relaxation time data and on the barrier is discussed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The V , value for C-18 of compound 4, with a methyl group at C-4 is 15.6 kJ/mol, which can be compared to the value of 14.4 kJ/mol found in 4,4-dimethyl adamantan-Zone (6). Both com- pounds have only one 1,3 diaxial CH, grouphydrogen interaction.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The V , value for C-18 of compound 4, with a methyl group at C-4 is 15.6 kJ/mol, which can be compared to the value of 14.4 kJ/mol found in 4,4-dimethyl adamantan-Zone (6). Both com- pounds have only one 1,3 diaxial CH, grouphydrogen interaction.…”
mentioning
confidence: 66%
“…They found that the use of Woessner's equation did not give satisfactory values for relatively concentrated solutions of borneol in CDC1,. Recently we have reported (6) the results for a number of norbornane and adamantane derivatives including borneol where satisfactory agreement was obtained between experimental values and those calculated using Woessner's equation for a symmetric top (1). The best correlation was obtained by assuming that the principal axis of the diffusion tensor passes through the heterosubstituent and the centre of mass of the molecule.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…No corrections for bulk magnetic susceptibility were made. The T, measurements were obtained by use of the standard inversion recovery technique as described previously (24). Results were treated using both an exponential three-parameter fit and a logarithmic plot.…”
Section: Methodsmentioning
confidence: 99%